2017
DOI: 10.3390/ijerph14091076
|View full text |Cite
|
Sign up to set email alerts
|

Poverty Dynamics and Academic Trajectories of Children of Immigrants

Abstract: Using Early Childhood Longitudinal Study, Kindergarten Class of 1998–1999 (ECLS-K), we investigated the relationship between poverty and academic trajectories for children in immigrant families in the United States. We used family socioeconomic status (SES) which considers parental education, parental occupation, and family income to define poverty in correspondence with the U.S. federal poverty threshold. Three dimensions of poverty were examined including depth (i.e., not-poor, near-poor, poor or extreme poo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…On the other hand, Chen et al (2015) examined the number sense performances among 4 th , 5 th , and 6 th grade local students, recent immigrants, and those with low socioeconomic levels in Taiwan, finding that new immigrant students in 6th grade had better number sense performances compared to other students. Having examined the relationship between poverty and the academic achievement of students in immigrant families, Zhang and Han (2017) stated that immigrant students outperformed local students from a certain poverty status.…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Chen et al (2015) examined the number sense performances among 4 th , 5 th , and 6 th grade local students, recent immigrants, and those with low socioeconomic levels in Taiwan, finding that new immigrant students in 6th grade had better number sense performances compared to other students. Having examined the relationship between poverty and the academic achievement of students in immigrant families, Zhang and Han (2017) stated that immigrant students outperformed local students from a certain poverty status.…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 99%
“…In a similar sense, there are studies in the literature that compare the number sense skills of immigrant students with others (Petersson, 2018;Votruba-Drzal et al, 2015;Zhang & Han, 2017) and that reveal the family factor as an important element in determining the number sense skills of immigrant students (Maulbeck, 2021;Takeuchi, 2016;Zamora, 2015). The present study is considered important in that the number of studies on immigrant students is limited; there is also a lack of studies that have focused on the number sense skills of Syrian immigrant students studying in multicultural secondary schools, on such skills in terms of students' gender and the duration of stay as an immigrant, as well as on such students' conceptual awareness of number sense components.…”
Section: Theoretical Frameworkmentioning
confidence: 97%
“…Studies have shown that simply classifying people as "in poverty" or "not in poverty" is not sufficient. 62 As we saw above, students living in deep poverty households often need social and physical supports above and beyond what is allocated for academics in a school or a school district. There is ample evidence of this need and considerable research on how additional funds can be wisely used to support students.…”
Section: Begin With Funding Adequacy and Equitymentioning
confidence: 99%